2013
DOI: 10.4161/cc.24289
|View full text |Cite
|
Sign up to set email alerts
|

Compartment-specific activation of PPARγ governs breast cancer tumor growth, via metabolic reprogramming and symbiosis

Abstract: The role of PPARγ in cancer therapy is controversial, with studies showing either pro-tumorigenic or antineoplastic effects. This debate is very clinically relevant, because PPARγ agonists are used as antidiabetic drugs. Here, we evaluated if the effects of PPARγ on tumorigenesis are determined by the cell type in which PPARγ is activated. Second, we examined if the metabolic changes induced by PPARγ, such as glycolysis and autophagy, play any role in the tumorigenic process. To this end, PPARγ was overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 67 publications
0
43
0
Order By: Relevance
“…PPARG is the best studied of the 3 PPAR subtypes and has been reported to have an anti-proliferative effect on breast cancer cells (Pon et al 2015) and is associated with better outcomes based on survival analysis of PPARG protein expression level in BC tissue microarrays (Abduljabbar et al 2015a). The downstream effect of PPARG seems to be dependent on the cell compartment in which PPARG is activated though, with activation in cancer cells resulting in growth inhibition while activation in stromal cells results in growth enhancement of co-injected breast cancer cells (Avena et al 2013). Recent studies have also suggested an involvement of PPARG and energy metabolism in breast cancer.…”
Section: Peroxisomementioning
confidence: 99%
See 1 more Smart Citation
“…PPARG is the best studied of the 3 PPAR subtypes and has been reported to have an anti-proliferative effect on breast cancer cells (Pon et al 2015) and is associated with better outcomes based on survival analysis of PPARG protein expression level in BC tissue microarrays (Abduljabbar et al 2015a). The downstream effect of PPARG seems to be dependent on the cell compartment in which PPARG is activated though, with activation in cancer cells resulting in growth inhibition while activation in stromal cells results in growth enhancement of co-injected breast cancer cells (Avena et al 2013). Recent studies have also suggested an involvement of PPARG and energy metabolism in breast cancer.…”
Section: Peroxisomementioning
confidence: 99%
“…Secondly, overexpression of PPARG in fibroblasts increased the production of l-lactate and mitochondrial dysfunction. In addition, PPARG induces the activation of HIF1A, a transcription factor that promotes glycolysis (Avena et al 2013).…”
Section: Peroxisomementioning
confidence: 99%
“…Vara et al [91] also pointed out that PPAR gamma knockdown with siRNA caused accumulation of the autophagy markers LC3-II and p62, suggesting that PPAR gamma was necessary for the autophagy flux. From another angle, Avena et al [92] reported that overexpressing PPAR gamma showed increased expression of autophagic markers, increased numbers of acidic autophagic vacuoles, increased production of L-lactate, cell hypertrophy and mitochondrial dysfunction. More interestingly, they [92] also presented that PPAR gamma can induce the activation of the two major transcription factors that promote autophagy and glycolysis in stromal cells, such as HIF-1 alpha and NF-kappa B.…”
Section: Newly Participant Of Autophagy Regulation: Pparsmentioning
confidence: 98%
“…Many investigators [88][89][90][91][92][93][94][95][96][97] reported that PPAR gamma was also involved in the control of transcriptional regulation of autophagy. The target genes of PPAR gamma has been reported including ATG7, ATG12, LC3, P62, ULK1, LAMP1, BCL2, Beclin1, Pink1, and Bnip3 [88][89][90][91][92][93][94][95][96][97] (Table 1). More specifically, Yan et al [88] discovered that PPAR gamma agonist troglitazone (TZ), a synthetic ligand of PPAR gamma, could induce autophagy and apoptosis in a variety of cancer cells.…”
Section: Newly Participant Of Autophagy Regulation: Pparsmentioning
confidence: 99%
See 1 more Smart Citation